PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) MENGGUNAKAN MEDIA KARTU KUARTET UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN PPKN KELAS V : Penelitian Tindakan Kelas - Lutfi Azizatun Nisaak; Wawan Shokib Rondli; Much Arsyad Fardani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Based on the results of conservation at SD 5 Klumpit, Kudus Regency, studentlearning outcomes in Civics and Indonesian subjects are still below the MinimumCompleteness Criteria (KKM). This is because the learning process is centered onthe teacher so that students are less active in participating in learning. The purposeof this study is to improve student learning outcomes using the Teams GamesTournamet (TGT) learning model using quartet card learning media. The methodused was Classroom Action Research which was conducted for 2 cycles with 2meetings in each 1 cycle. By using observation data collection techiques and test.The subjects of this research were all fifth grade students at SD 5 Klumpit. In cyclesI and II, PPKn subjects obtained a classical completeness result of 72% to 88%,while the Indonesian language subject obtained a classical completeness of 72% incycle I to 76% in cycle II. From these results it can be concluded that the TGTlearning model using quartet card media can improve student learning outcomes.